Effect of clay and of electrospinning on the polymorphism, structure and morphology of poly(vinylidene fluoride) - Neppalli, Ramesh; Wanjale, Santosh; Birajdar, Mallinath S.; Causin, Valerio (European Polymer Journal, 2013)
Electrospun poly(vinylidene fluoride) (PVDF) fibers, containing different amounts of montmorillonite clay were produced, in order to study the effect of clay and of the electrospinning process on the polymorphism, structure and morphology of the PVDF matrix, Clay acted as a processing aid agent, avoiding the formation of beads and improving the quality of the fibers. Clay and the electrospinning process acted synergically on the chain mobility, favoring the formation of beta phase of PVDF, the most valuable for its piezoelectric properties, and shaping its semicrystalline morphology. Electrospinning did not significantly aid the dispersion of clay within the matrix. The interplay of formulation and processing in these composites allowed to obtain PVDF-based materials with varying polymorphism, structure and morphology, offering the possibility to ultimately control their functional properties. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Composite; electrospinning; Poly(vinylidene fluoride); Polymer; polymorphism; SAXS

Morphology, polymorphism, and metal ion adsorption studies of electrospun nanofibers based on pvdf and organically modified layered double hydroxide - Birajdar, Mallinath S.; Wanjale, Santosh D.; Lonkar, Sunil P. (Journal of Applied Polymer Science, 2013)
Nonwoven nanofiber mats of polyvinylidene fluoride (PVDF) with modified layered double hydroxide (MLDH) were prepared by electrospinning. The fiber morphology was studied using scanning electron microscopy. X-ray diffraction and FTIR spectroscopy was used to characterize the polymorphism in electrospun mats. Fibers of diameter in the range 80-800 nm with beads of about 2-3 mu m size were observed for pure PVDF, while in case of PVDF/MLDH nanocomposites the number and size of beads were found to be significantly reduced. Uniform and fine nanofibers were obtained at lower content of MLDH, but slightly rough surface was seen for higher content. FTIR and X-ray diffraction patterns signify various crystalline forms of electrospun PVDF. The content of polar -crystalline phase of PVDF, which exhibit piezo and ferroelectric properties was found to be enhanced significantly due to reinforcement of MLDH. Use of these nanofiber mats for heavy metal Cu (II) removal was explored. (c) 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 4508-4515, 2013
Keywords: Adsorption; electrospinning; fibers

Studies on fabrication, characterization, and metal extraction using metal chelating nonwoven nanofiber mats of poly(vinyl alcohol) and sodium alginate blends - Rathna, G. V. N.; Birajdar, Mallinath S.; Bhagwani, Manish; Paul, V. L. (Polymer Engineering and Science, 2013)
Poly(vinyl alcohol) and sodium alginate blends with and without the metal chelate, bis(2,4,4-trimethylpentyl)phosphinic acid were prepared in various compositions and fabricated to stable nanofibers and films to evaluate their efficacy for metals adsorption and desorption. Surface morphology of the nanofibers was characterized by scanning electron microscopy. The solution properties and variation in content of sodium alginate in the feed mixture have influenced morphology of nanofibers. However, influence of bis(2,4,4-trimethylpentyl)phosphinic acid was insignificant. The films and nanofibers were characterized using Fourier transform infrared spectroscopy, differential scanning calorimetry, thermo gravimetric analysis, and X-ray diffraction to understand compatibility between polymers, thermal stability, decomposition temperature, and variations in crystallinity. Metal adsorption studies for nanofiber mats comprising bis(2,4,4-trimethylpentyl)phosphinic acid were demonstrated using copper (II), cobalt(II), and nickel(II) salts. The nanofibers adsorbed more copper (363 mg/g) when compared with films (105 mg/g). Nanofiber mats immobilized with bis(2,4,4-trimethylpentyl)phosphinic acid adsorbed copper in greater magnitude (497 mg/g) than nanofiber mats without bis(2,4,4-trimethylpentyl)phosphinic acid (363 mg/g). However, adsorption of cobalt and nickel was very low to be detected. The metal adsorption and desorption studies were also confirmed by energy dispersive X-ray spectroscopy. POLYM. ENG. SCI., 2013. (c) 2012 Society of Plastics Engineers

Polystyrene/TiO2 composite electrospun fibers as fillers for poly(butylene succinate-co-adipate): Structure, morphology and properties - Neppalli, Ramesh; Causin, Valerio; Benetti, Edmondo Maria; Ray, Suprakas Sinha; Esposito, Antonella; Wanjale, Santosh; Birajdar, Mallinath S.; Saiter, Jean-Marc; Marigo, Antonio (European Polymer Journal, 2014)
In this work, composite polystyrene/titanium dioxide (PS/TiO2) electrospun fibers were used as a reinforcement for a poly(butylene succinate-co-adipate) (PBSA) matrix. The structure, morphology, mechanical properties and degradation behavior of such materials were investigated, finding that, as a function of their TiO2 content, the fibers exerted different effects. The main mechanism through which the fibers modified the structure and morphology of the polymer matrix is by altering its crystallization kinetics. The presence of TiO2 modified the roughness of the fibers and therefore affected the interfacial adhesion between the filler and the matrix. The modulus of PBSA was improved, even though the brittleness of the materials was increased by the presence of the fibers. Different amounts of TiO2 within the fibers allowed to tune the hydrolytic degradation rate of the composites. This paper shows the potential of using composite electrospun fibers as effective fillers for the preparation of polymer-based composites. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Biodegradable polymers; Degradation; electrospinning; Morphology; Nanocomposites; Polycaprolactone

Surface tailored PS/TiO2 composite nanofiber membrane for copper removal from water - Wanjale, Santosh; Birajdar, Mallinath S.; Jog, Jyoti Prakash; Neppalli, Ramesh; Causin, Valerio; Karger-Kocsis, Jozsef; Lee, Jonghwi; Panzade, Prasad (Journal of Colloid and Interface Science, 2016)
Polystyrene (PS)/TiO2 composite nanofiber membranes have been fabricated by electrospinning process for Cu2+ ions removal from water. The surface properties of the polystyrene nanofibers were modulated by introducing TiO2 nanoparticles. The contact angle of the PS nanofiber membrane was found to be decreased with increasing concentration of TiO2, depicted enhanced hydrophilicity. These membranes were highly effective in adsorbing Cu2+ ions from water. The adsorption capacity of these membranes was found to be 522 mg/g, which is significantly higher than the results reported by other researchers. This was attributed to enhanced hydrophilicity of the PS/TiO2 composite nanofiber membranes and effective adsorption property of TiO2 nanoparticles. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: electrospinning; Metal ion adsorption; Nanofiber; TiO2; Water treatment/purification